Prevalence of foodborne pathogens isolated from retail freshwater fish and shellfish in China. (May 2019) - Li, Ying; Pei, Xiaoyan; Yan, Jun; Liu, Danru; Zhang, Huaning; Yu, Bo; Li, Ning; Yang, Dajin
Abstract: In 2016, the nationwide food safety surveillance was conducted on fresh water fish and shellfish in China. The prevalence of Vibrio parahaemolyticus, Vibrio cholerae, Salmonella, and L. monocytogenes were 19.0% (613/3226), 3.4% (110/3226), 3.8% (124/3226), and 2.5% (80/3226), respectively. The tdh and trh genes were detected in 19 (2.6%) and 24 (3.3%) of the 718 V. parahaemolyticus isolates, respectively. All V. cholerae strains were confirmed as non-O1/O139 serogroups. The most predominant Salmonella serotypes were S. Stanley, S. Thompson, S. Litchfield, S. Typhimurium, S. Virchow, S. Carrau, and S. Infantis . The results of this comprehensive survey showed contamination by four pathogens in fresh water fish and shellfish in China for the first time. The study indicated a need for proper handling, storage, and cooking of freshwater fish and shellfish. Further risk reduction assessment and implementation are necessary to reduce foodborne disease in China. Highlights: ● Results provide comprehensive data about pathogens in freshwater products in China ● We analyse the prevalence of different pathogens in fish, crustaceans and molluscs ● Qualitative and quantitative tests, virulence genes of V. parahaemolyticus were done